The Effect of Liquidity, Leverage, Efficiency, and Inflation on Financial Performance - Febriyanti, Giany; Simon, Zainal Zawir; Oktavia, Dinda (SAN Scientific, 2024)
This research investigates the influence of liquidity, leverage, total asset turnover ratio, and inflation on the financial performance of food and beverage companies listed on the Indonesia Stock Exchange from 2018 to 2022. Using a quantitative research method with secondary data and a purposive sampling method, 19 companies were selected for analysis. The research employed panel data analysis combining time series and cross-sectional data. The findings reveal that collectively, variables such as current ratio, debt to equity ratio, total asset turnover ratio, debt to total asset ratio, and inflation significantly impact financial performance. However, when examined individually, the current ratio and debt to total asset ratio show a negative and insignificant influence, while the debt to equity ratio displays a positive yet insignificant effect. Conversely, the total asset turnover ratio and inflation demonstrate a positive and significant impact on financial performance. This research underscores the managerial implications concerning the importance of monitoring specific financial ratios in decision-making processes, particularly in managing liquidity and asset efficiency. Managers are advised to consider inflation factors in financial planning and decision-making to optimize financial performance.